Ocean literacies: the promise of regional approaches integrating ocean histories and psychologies - Schwerdtner Manez, Kathleen; Stoll-Kleemann, Susanne; Rozwadowski, Helen M. (Frontiers in Marine Science, 2023)
The current concept of ocean literacy reflects a prerequisite for achieving ocean sustainability.Existing ocean literacy reflects a fundamentally western view of oceans that works in tension with ocean literacy goals. Although ocean literacy practitioners and researchers are, laudably, starting to incorporate Indigenous knowledges and perspectives from BIPOC communities, attention to historical change continues to be left out of ocean literacy, to the detriment of ocean literacy goals. This article points out that, given the reality that human-ocean relationships have changed over time, and differed among cultural groups in the past as well as in the present, ocean literacy needs to incorporate ocean history at a foundational level.Because there are historical differences in human relationships with oceans, it stands to reason that regional ocean literacies must be more effective than a universal and timeless ocean literacy framework. Following the logical efficacy of a regional approach to ocean literacy, this article further argues that regional ocean literacies should involve the systematic inclusion of emotional elements. Regional ocean literacies should be constructed through knowledge co-production, involving diverse types of expertise, knowledge and actors to produce contextspecific knowledge and pathways towards a sustainable future. To fully exploit the potential of ocean literacy, there is a need for the UN Ocean Decade to work towards regional and place-based approaches that incorporate history as well as culture in an iterative and collaborative processes involving diverse types of expertise, knowledge and actors.